EDUKASI COVID-19 DAN VAKSINASI BAGI MASYARAKAT DI KAMPUNG BATU BUSUAK KECAMATAN PAUH KOTA PADANG - Saptino Miro; Roza Kurniati; Dwitya Elvira; Arina Widya Murni; Raveinal Raveinal; Alexander Kam (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Infectious diseases are still a major health issue that requires serious treatment. The covid-19 is now one of the significant infectious diseases worldwide marked by rapid contagion and global spread. The world health organization (who) has defined covid-19 as a global pandemic and the government has set public health emergencies in Indonesia, obliging countermeasures. The covid-19 countermeasures should continue massively with several strategies. In addition to promotive strategies and the application of health protocols, another effective strategy is needed to break off the chain of disease transmission through vaccination efforts. The purpose of the activity is to do the education about covid-19 and the covid-19 vaccination of the people in Kampung Batu Busuak, Kelurahan Limau Manis, Kecamatan Pauh, Padang. The implementation of this activity includes the counseling of covid-19 and the covid-19 vaccination on Saturday, November 13th, 2021. Before counseling, the Questionnaire was issued to assess a public knowledge level on covid-19 and a covid-19 vaccination. From a questionnaire on covid-19 and covid-19 vaccination, the total of people who have already been vaccinated twice is 22 people and 4 with the covid-19 vaccine once. Therefore, still needed counseling about covid-19 and covid-19 vaccination to enhance awareness of the society towards the importance of covid-19 vaccination.